Social Interaction of the Baha'i Community in Fostering Peace in a Multicultural Society in Kubu Raya - Mimi Anggraini; Tiara Sari; Sulaiman; Muhammad Hiqqal (ASTEEC, 2025)
Kubu Raya is one of the regencies located in West Kalimantan, which has a diverse range of ethnicities, cultures, traditions, and religions. This study aims to examine the social interactions of the Bahá'í community in fostering peace in a multicultural society in Kubu Raya Regency, West Kalimantan. The community of Kubu Raya is known for its ethnic, religious, and cultural diversity, which has the potential to create challenges in social relations. As one of the minority groups, the Bahá'í community upholds values that emphasize the unity of mankind, tolerance, and peace. This research employs a qualitative method with a sociological approach, and the data sources consist of primary and secondary sources. Data collection is conducted through observation, interviews, and Focus Group Discussions, while data analysis is carried out through data condensation, data display, and conclusion drawing. The results of this study indicate the significant role of the Bahá'í community in fostering harmony amidst diversity. The Bahá'í teachings emphasize the principles of human unity, tolerance, cooperation, and cultural understanding. The Bahá'í community in Kubu Raya strives to build respectful and supportive relationships among residents, despite their diverse backgrounds. Bahá'ís are actively involved in social and cultural activities that engage all layers of society, strengthening mutual understanding and promoting inclusivity. They also instill values of peace based on their religious teachings, which prioritize peace, unity, and social justice. The social interactions of the Bahá'í community in the multicultural context of Kubu Raya not only focus on togetherness in diversity but also contribute significantly to sustainable peace, strengthening social bonds, and maintaining social stability in the face of ongoing social dynamics.